Case report: stent dislodgedment - Oktaviono, Yudi Her (Folia Medica Indonesiana, 2017)
Male 61 years old who presented with stable angina since 1 month ago, with Risk factor of CAD: hypertension, Dyslipidemia and heavy smoker. The ECG showed inferior old myocardial infarction. Diagnostic coronary angiography found: bifurcatio lesion at distal LMCA with significant stenosis 60% at the distal LM and 85% at the osteal LCx (Medina score 1-1-0), high D1 and diffuse disease with maximal stenosis 85% at the distal LAD after D2, Significant stenosis 85% at the osteal LCx and CTO at the distal after OM1, diffuse disease with maximal stenosis 85% at the mid RCA. A 6-Fr JR 4.0 guiding catheter (Launcher, Medtronic) was engaged into the right coronary artery ostium via the femoral artery. GW pilot 50 (Hi-Torque Pilot 50) inserted to distal RCA. Perform Balloon support by Saphire II inserted to mid RCA and dilated, after that perform balloon to proximal RCA and dilated. Stent DES Firebird II (Rapamycin) to mid RCA and dilated. Stent BMS Apollo 3.0x36 mm inserted to proximal-mid RCA, overlapping with previous stent, but was loss or dislodged and insert to the guiding catheter. BMS stent was pulled out with small balloon ex stent. GC 6F 4.0 inserted to ascending Aorta and engaged at ostium RCA. BMS stent Arthos PICO 3.0x 34 mm inserted to proximal-mid RCA, overlapping with previous stent and dilated. Final angiography confirmed successful pull out of loss stent and dilation of the RCA.